PENGARUH KOMPENSASI DAN INSENTIF TERHADAP MOTIVASI KARYAWAN DALAM PERUSAHAAN DEALER KENDARAAN DI TANGERANG SELATAN - Utama, Zahera Mega; Saputro, Andriyanto; Sintanis, Dini; Nuraeny, Virna (Jurnal Pijar, 2025)
This study aims to determine the effect of compensation and incentives on employee motivation in the vehicle sales sector in South Tangerang. In the automotive industry, it is very important to maintain and enhance employee morale, as it affects the level of sales, especially considering the intense competition in this field. The research method used in this study is qualitative, utilizing in-depth interview techniques with informants working at various vehicle dealerships, both two-wheel and four-wheel, located throughout South Tangerang. The results of the study indicate that both compensation and incentives have a positive and significant impact on employee motivation. Providing fair and transparent incentives has been proven to increase employee motivation, leading to greater enthusiasm at work and higher sales performance.